Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

DNA ‐based identification of anadromous fishes ( Alosa spp., Family Clupeidae ) in stomach contents of marine groundfish - Landon P. Falke; Stacy Rowe; Yuan Liu; Timothy F. Sheehan (Journal of Fish Biology, 2026)
Using DNA techniques for prey identification is an emerging approach for enhancing the precision and accuracy of trophic information. We evaluated the effectiveness of DNA‐based prey identification in conjunction with visual stomach content analysis of commercially important groundfish in the nearshore Gulf of Maine, with a focus on distinguishing consumed anadromous ( Alosa spp.) and closely related marine prey (Atlantic herring Clupea harengus , Atlantic menhaden Brevoortia tyrannus ). DNA barcoding of 179 consumed prey specimens provided species‐ or genus‐level identification in 122 cases (68.2%), including 104 improvements to taxonomic resolution and three conflicting results compared to visual identifications. Combining DNA‐based identifications of partially or well‐digested prey with the broader visual analysis substantially improved quantification of a diet metric, frequency occurrence, as a proxy for the relative diet contributions of anadromous and marine clupeids. Body size measurements of consumed Alosa spp. identified using DNA were consistent with year‐0 or year‐1 juvenile life stages. Possible limitations to success rates of DNA assignment included the quality of sample preservation (ethanol), reference database quality (accuracy of voucher specimen identification) and sequencing errors (miscalling of nucleotide bases). Despite this, the integration of molecular methods substantially improved the interpretability of trophic interactions involving morphologically similar prey with ecologically important differences in life history. These results highlight how the targeted application of DNA‐based prey identification can complement conventional diet analyses by improving the quantification of trophic interactions that ultimately govern ecosystem processes.

Trophic ecology of groundfishes in nearshore areas of the Gulf of Maine - Landon P. Falke; Brian E. Smith; Stacy Rowe; Rebecca J. Peters; Timothy F. Sheehan (Journal of Fish Biology, 2025)
Ecosystem management requires an integrated understanding of ecological interactions. In the Gulf of Maine (GoM), trophic information pertaining to commercially important groundfishes and nearshore prey communities is lacking. We characterized nearshore communities and groundfish diets using data collected from nearshore surveys (864 bottom trawls and 3638 stomach samples of six groundfish species) conducted biannually (spring and fall) in Midcoast Maine and Penobscot Bay from 2012 to 2022. Groundfish diets were dominated by some of the most available nearshore prey (gadiform and clupeiform fishes and pandalid and crangonid shrimps). Shifts in relative prey availability over environmental gradients (e.g., depth and position along the coast), across seasons, and over years corresponded with parallel patterns in prey contributions to groundfish diets in specific predator–prey interactions. Negative trends in the relative availability and diet occurrence of signature GoM prey taxa (Northern shrimp Pandalus borealis , Atlantic herring Clupea harengus , and euphausiids) indicate that broader ecosystem changes, such as steady rises in water temperature and shifts in species distributions, are impacting nearshore trophic dynamics in the GoM. These observations provide timely information on mechanisms that underlie groundfish productivity and warrant inclusion of nearshore trophic dynamics in relevant ecosystem models.

Food web ecology of Gulf Stream flounder ( Citharichthys arctifrons ): a continental shelf perspective - Stacy Rowe; Brian E. Smith (Journal of Fish Biology, 2022)
Gulf Stream flounder, Citharichthys arctifrons , are regularly observed in fish diets of the northeast U.S. continental shelf, yet lack commercial value and are often ignored. Similarly, Gulf Stream flounder diets of the Northwest Atlantic have remained largely unexamined, except for a brief period from 1976 to 1980. To better understand their role in the ecosystem, juvenile through adult Gulf Stream flounder were examined both as a predator and prey, and the magnitude of their feeding footprint (removal of prey biomass) was quantified for the northeast U.S. continental shelf. Their stomachs were sampled from 2005 to 2010, with the majority examined in the field macroscopically. Due to large proportions of unidentifiable prey, the effort was expanded in 2011–2012, and all stomachs were processed in the laboratory microscopically. Gulf Stream flounder were consumed by 15 fish, and what they eat (percentage mass and percentage frequency of occurrence) was documented by season, spatial region and year. Highly benthivorous, Gammaridea and Polychaeta dominated the diet in all years, seasons and regions, but Ophiuroidea (brittle stars) were also prominent in Southern New England during the spring. Gulf Stream flounder diets remained consistent across regions and time, with only a few feeding differences between seasons and one region. Relative to the productivity of benthos for this shelf ecosystem, the feeding footprint of Gulf Stream flounder was minor for their predominant benthic prey with a maximum percentage of benthos production eaten of 0.01% m −2 in Southern New England. With an ecosystem perspective, this feeding information offers a foundation for improving fisheries management among shared living marine resources considering benthic habitat and prey availability.

Social integration of translocated wildlife: a case study of rehabilitated and released elephant calves in northern Kenya - Shifra Z. Goldenberg; Stephen M. Chege; Nelson Mwangi; Ian Craig; David Daballen; Iain Douglas-Hamilton; Nadine Lamberski; Moses Lenaipa; Reuben Lendira; Colman Lesowapir; Lekilia P. Lokooria; Mathew Mutinda; et al. (Mammalian Biology, 2022)
Conservation translocations have the potential to strengthen populations of threatened and endangered species, but facilitating integration of translocated individuals with resident populations remains a substantial challenge. Developing functional social relationships like cooperative partnerships or establishing clear dominance hierarchies may be critical to integration of released individuals. Developing such relationships has not received much attention in translocation research, especially for long-lived, socially complex animals for which establishment and navigation of social environments is often a lengthy process that requires sustained monitoring to understand. Here, we present a case study of the social associations of African savannah elephant ( Loxodonta africana ) calves that have been rehabilitated and released into a fenced wildlife sanctuary in northern Kenya with a resident population of elephants. We use focal follows of interactions pre-release and GPS tracking post-release to quantify social associations of calves with each other and with resident elephants at the release site. We demonstrate how this approach supports translocation monitoring by capturing temporal trends in social patterns within and between release cohorts and among released elephants and wild elephants already resident at the site during a transitional soft release period. Our results show that initial post-release social behavior of rehabilitated calves is related to histories of interaction with familiar individuals and cohort membership and that released calves increased their associations with residents over time. This information provides new behavioral insights for guiding elephant release projects, like the strength of relationships within and among release cohorts, the time to integration with the resident population, and the occurrence and increased incidence of societal fission–fusion. Further, this study provides an example of the utility of animal behavior research to achieve and assess progress towards conservation objectives, and to develop monitoring tools for conservation managers.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.